(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The study addresses the fundamental role and relevance of women in the development of the Rap musical genre in the city of So Gonalo, in Rio de Janeiro and in Brazil. Despite facing obstacles such as sexism and lack of recognition, Rappers have shown resistance and creativity, creating their own space in the rhythm. Her authentic lyrics reflect personal and social experiences, challenging stereotypes and redefining the role of women in the Hip Hop movement. In addition to music, these artists serve as leaders and activists, using their influence to empower other young women. Thus, the research celebrates the influence of these women, who transformed Rap into a movement of social and cultural change.